"Everything Created by God Is Pure". The Image of God in Emanuel Vigeland’s Programme of Art in His Tomba Emmanuelle in Oslo - Wadell, Maj-Brit (Scripta Instituti Donneriani Aboensis, 1996)
Quicquid Deus creavit purum est — Everything created by God is pure. The Norwegian artist Emanuel Vigeland (1875-1948) had these words inscribed above the entrance to his mausoleum, Tomba Emmanuelle, in Oslo. They may be interpreted as a type of creed, exemplified and illustrated by the paintings and sculptures on the theme of Vita (life) which Vigeland had completed in the mausoleum from 1927 up until his death more than 20 years later. In this article, the author attempts to explain the nature of the image of God visualized by Emanuel Vigeland when he carried out the artistic decoration of the burial chamber-to-be. The author describes and interprets the large painting on the far wall as well as the accompanying text. To start with, she offers a brief description of the artist’s background, with special attention to his upbringing and childhood environment, which can be seen as crucial in the development of his view of life. This presentation is based on many years’ study of original sources concerning Emanuel Vigeland’s life and works.